2021
DOI: 10.3390/s21020457
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study on Condition Diagnosis for Thrust Bearings in Oscillating Water Column Type Wave Power Systems

Abstract: In order to utilize wave energy, various wave power systems are being actively researched and developed and interest in them is increasing. To maximize the operational efficiency, it is very important to monitor and maintain the fault of components of the system. In recent years, interest in the management cost, high reliability and facility utilization of such systems has increased. In this regard, fault diagnosis technology including fault factor analysis and fault reproduction is drawing attention as an imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…In this way, features potentially representing faults are extracted from the sensor data. After that, we reduce the dimension of the features, and build the fault classification map represented by the features through several statistical methods, e.g., principal component analysis (PCA) and the Bayesian classifier [25][26][27]. In the classifier learning process, previous fault history information and normal operation status information are used as the learning data of the fault classifier in the supervised learning scheme.…”
Section: Detailed Procedures For Fault Diagnosismentioning
confidence: 99%
See 2 more Smart Citations
“…In this way, features potentially representing faults are extracted from the sensor data. After that, we reduce the dimension of the features, and build the fault classification map represented by the features through several statistical methods, e.g., principal component analysis (PCA) and the Bayesian classifier [25][26][27]. In the classifier learning process, previous fault history information and normal operation status information are used as the learning data of the fault classifier in the supervised learning scheme.…”
Section: Detailed Procedures For Fault Diagnosismentioning
confidence: 99%
“…Sci. 2021, 11, x FOR PEER REVIEW 4 of 15 statistical methods, e.g., principal component analysis (PCA) and the Bayesian classifier [25][26][27]. In the classifier learning process, previous fault history information and normal operation status information are used as the learning data of the fault classifier in the supervised learning scheme.…”
Section: Detailed Procedures For Fault Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the FMEA process is used in the design and validation of a hydraulic torque converter [5]. Additionally, the diagnosis of the bearing condition using the FMEA process is presented in [6]. Additionally, in [7], Bayesian networks are built from the FMEA process used by Markov decision processes to model uncertainties within unmanned aerial vehicles.…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al used image shadow removal and color model binarization, then used the Hough transform to find the switch, and finally identified and compared the switch state [3]. To determine the state of the switch, Kim et al found the switch symbol associated with the circuit breaker switch and performed gray-scale conversion, binarization, smoothing, character extraction, and character pattern matching in the map area of the symbol [4]. Jalil et al proposed a method for evaluating the state of power grid equipment online using multiple measurements.…”
Section: Introductionmentioning
confidence: 99%